Physiopathology of vesico-ureteral reflux. Issue 1 (December 2016) - Arena, Salvatore; Iacona, Roberta; Impellizzeri, Pietro; Russo, Tiziana; Marseglia, Lucia; Gitto, Eloisa; Romeo, Carmelo
Abstract Vescico-Ureteral Reflux (VUR) is a common condition in childhood, caused by a congenital anomaly at the Vescico-Ureteral Junction (VUJ) level. It seems that the main cause could be an abnormal embryological development occurred during the early stage of fetal life. Refluxing ureteral endings show structural and functional anomalies: previous studies have shown a significant decrease in alfa actin, miosin and desmin contents as well as an high rate of atrophy and muscular degeneration with disorganized muscular fibres. The roles played by Cajal cells and Connexin 43 in generating peristaltic waves appears to be fundamental for the physiological VUJ function and activity. Attention was focused also on the congenital muscular deficiency of the RUs, on regard to general morphology, smooth muscle cells architecture, inflammatory markers and the distribution of collagen composition. This review will discuss and investigate the importance of the modified configuration of Sarcoglycan (SG) sub complex (particularly the deficiency of the ε-SG and the increased expression of the α-SG), the role played by Cajal Cells, the intravescical tunnel length to ureteral diameter ratio as possible causes of the functional alterations in the refluxing ureteral ends leading towards the VUJ incompetence.